Spreminjanje podnebja v holocenu - Ogrin, Darko (Geografski vestnik, 2005)
The paper presents the principal features of the climatic changes in the Holocene and a short overview of the paleoclimatic reconstruction methods. The Younger Dryas (10.000 to 11.000 years ago) was a transition of the last ice age to the Holocene. The warmest period of the Holocene, the altithermal, occurred between 6000 and 3000 B. C., and was followed by a period of cooler climatic conditions. Between 500 and 1300 A.D. there was the medieval climatic optimum which turned to the Little Ice Age after 1450. Characteristic of the last two centuries, for which multi-year strings of climatic measurements are available, is a gradual increase in air temperatures.
Keywords: klimatogeografija; paleoklimatologija; klimatske spremembe; podnebne spremembe; holocen; Slovenia; Slovenija